Bank loan rate indexation in the Eurocurrency market - Savvides, Andreas (My University, 1987)
This paper demonstrates that commercial bank indexation of the interest rate charged on loans to developing countries through the Eurocurrency market has differential effects on prime and non-prime borrowers. If loan contracts are indexed, the interest rate adjustment to non-prime borrowers, following an increase in the cost of funds to the bank, will be greater than that which a profit-maximizing bank would desire. As a result, it is proposed that the proportion of loan commitments drawn down by non-prime borrowers declines when the cost of bank funds rises. An analysis with data from developing-country borrowings confirms this proposition. © 1987.